ANALYSIS OF FOREIGN AND NATIONAL EXPERIENCES IN DEVELOPING STUDENTS’ READING COMPETENCE (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes foreign and national experiences in developing students’ reading competence.The study highlights the role of communicative, cognitive, and intercultural approaches in formingreading skills, emphasizing the interactive and reflective aspects of reading activities in moderneducation. A comparative analysis between the educational practices of the European Union, theUnited States, Japan, and Uzbekistan reveals effective strategies. The findings justify the need forusing innovative technologies, individualized learning environments, and reflective methods toenhance students’ reading competence effectively